Responsive Fluorescent Coumarin–Cinnamic Acid Conjugates for α-Glucosidase Detection - Luo, Dong; Zhang, Xin; Li, Xiaoying; Zhen, Yi-Yu; Zeng, Xingyi; Xiong, Zhuang; Zhang, Yinghui; Li, Hongguang (Frontiers in Chemistry, 2022)
α-Glucosidase is a potent drug target for treating type II diabetes mellitus. A great number of α-glucosidase inhibitors have been developed based on the molecular skeletons of bioactive natural products. However, efficient fluorescent probes for α-glucosidase detection are still limited, not to mention the probes with additional inhibitory functions. In this work, aiming for the enzyme’s highly specific detection, we designed and synthesized two environmentally sensitive fluorescent probes, namely, LD01 and LD02, respectively, based on conjugates of coumarin and cinnamic acid derivatives. We found a significant responsive emission enhancement upon LD02’s binding to α-glucosidase. These newly designed probes can act as a simple but efficient tool to evaluate the binding affinity of α-glucosidase to their inhibitors.